The effects of some antibiotics on polymorphonuclear leukocyte functions of elderly patients in vitro before and after zinc supplementation - SOYOĞUL GÜRER, ÜMRAN (ELSEVIER, 2006)
The effects of ciprofloxacin, cefodizime, rifampicine, doxycycline and cefodizime+rifampicine combination on polymorphonuclear leukocyte (PMN) functions (phagocytosis and intracellular killing activity) were investigated in vitro in elderly patients and compared with those of healthy young volunteers before and after zinc supplementation. PMNs of 13 elderly hypertensive patients and 10 healthy young volunteers were isolated by Ficoll-Hypaque gradient centrifugation method from venous blood with EDTA. The subjects were given 22 mg/daily/oral zinc supplementation for I month. Serum zinc levels before and after supplementation were measured by flame atomic absorbtion spectrophotometer and the effects of each drug on PMN functions at therapeutic concentrations were investigated. Ciprofloxacin significantly increased the PMN's phagocytic activity of elderly patients (p=0.002) before zinc supplementation and significantly increased both PMN functions of elderly patients (p=0.002) after zinc supplementation. The same antibiotic significantly increased both PMN functions of healthy young volunteers (p = 0.005 and p < 0.05, respectively) before and after zinc supplementation when compared with the control (drug-free). Cefodizime significantly increased the PMN's phagocytic activity of elderly patients (p=0.003, p=0.002) before and after zinc supplementation when compared with the control (drug-free). It also significantly increased both PMN functions of healthy young volunteers (p=0.005 and p < 0.05, respectively) before and after zinc supplementation when compared with the control (drug-free). Doxycycline significantly increased PMN's intracellular killing activity of healthy young volunteers before zinc supplementation (p < 0.05) when compared with the control (drug-free) values. Rifampicine significantly decreased PMN's phagocytic activity of elderly patients (p < 0.05) after zinc supplementation. Cefodizime+rifampicine combination significantly increased PMN's phagocytic activity at therapeutic concentrations of healthy young volunteers (p=0.005) before zinc supplementation and PMN's phagocytic activity of elderly patients (p < 0.05) after zinc supplementation when compared with the control (drug-free). Consequently, in the present study from the antibiotics ciprofloxacin, cefodizime and cefodizime+rifampicine combination, which are accepted as biological response modifiers have demonstrated stimulatory effects by significantly increasing polymorphonuclear leucocyte functions (phagocytosis and/or intracellular killing activity) of elderly patients and healthy young volunteers in vitro before and safter zinc supplementation. Additionally zinc supplementation has more immunostimulatory effects on PM functions of healthy young volunteers than elderly patients. (c) 2005 Published by Elsevier B.V.
Keywords: polymorphonuclear leukocyte functions; phagocytosis; intracellular killing; antibiotics; elderly; zinc supplementation; ANTITUBERCULOUS DRUGS; CEFODIZIME; NEUTROPHIL; DOXYCYCLINE; AGE